The Phenomenon of Muslim Influencers and Qur’anic Interpreters in the Digital Space: A Study of Ismail Al-Ascholy’s Interactions on the Instagram Account @ismailascholy - Muhammad Habib Izzuddin Amin; Kholifa Haidira; Asniah (Jurnal test, 2025)
This article analyzes Ismail Al-Ascholy’s interaction patterns on his Instagram account @ismailascholy, focusing on the formation of interpretive authority in digital dakwah. This study uses a netnography approach to examine the interaction between Ismail Al-Ascholy and his followers, as well as Max Weber’s authority framework to explore the types of authority he possesses. The analysis reveals that Ismail Al-Ascholy embodies traditional and charismatic religious authority. His traditional authority stems from cultural legitimacy through his lineage as a descendant of Kyai Khalil Bangkalan, a prominent religious scholar, and his position as the leader of a pesantren. His charismatic authority is formed through personal appeal via persuasive communication style, emotionally resonant spiritual narratives, and direct interactions that build trust and strengthen his charisma on social media. Using a netnographic approach, it was found that interactions on the Instagram account @ismailascholy are participatory and interactive, where followers actively contribute to interpretive discourse. Followers engage in discussions, question and answer sessions, and the dissemination of tafsir content. These findings indicate that digital dakwah is changing religious relationship patterns, where the authority of tafsir is not only determined by traditional religious structures but also by social dynamics that develop in virtual spaces, creating an authority that is more flexible and responsive to the needs of followers.